Numeričke metode rješavanja nelinearnih jednadžbi u određivanju prosječne brzine vozila - Šikić, Tomislav; Gjumbir, Marijana (Promet - Traffic&Transportation, 2012)
This paper gives recommendations for the application of Pegasus numerical algorithm for establishing the parameters needed for the computation of average vehicle speeds on two- way roads. The tables made by worked out by means of this method enable the substitution of incorrect diagrams that have been used up to this point of time.